Construir una ciudad para la memoria: Canto a su amor desaparecido de Raul Zurita - Garrido Alarcón, Edmundo (Revista de Filología Románica, 2009)
A reading of Canto a su amor desaparecido by the chilean poet Raul Zurita, appeared during the military dictatorship in Chile, is proposed from a perspective that combines anthropology and history to understand its formal configuration as a necropolis for the disappeared from Chile and other peripheral countries of the West. This spatial configuration should allow a transposition, as a lieu de mémoire, the denied facts in a City of memory. Following the anthropological scheme of mourning, this lieu de mémoire is the necessary space for the society to enact mourning for the disappeared. The importance of the formal configuration is emphasized, the use of concrete poems (calligrammes) in the shape of niches and maps that stress the spatial character of the poem’s composition. In the heyday of postmodernist skepticism Zurita’s affirmative proposition gives a place for mourning and hope.